Waldenström Macroglobulinemia: Clinico-pathological Profile and Treatment Outcomes of Patients from a Tertiary Care Centre of North India - Kumar, Sujeet (Indian J Hematol Blood Transfus, 2020)
Waldenstorms Macroglobulinemia (WM) is a rare mature B cell neoplasm characterized by a lymphoplasmacytic lymphoma and an IgM monoclonal protein. It is managed by Rituximab based chemotherapy. A single-centre retrospective study was carried out to analyse the clinical presentation, laboratory features, and treatment outcomes of all consecutive patients of WM, diagnosed over a period of 86 months. First-line treatment regimens included RCD (Rituximab/Cyclophosphamide/Dexamethasone), BDR (Bortezomib /Dexamethasone/ Rituximab) and (Lenalidomide/Dexamethasone). A total of 26 patients of WM were diagnosed during this period, with a median age of 65 years. Majority (89%) of these patients were of intermediate (47%) to high risk (42%). An overall response rate of 76.4% was achieved. RCD was found superior to BDR in terms of treatment response. For those who required 2nd line chemotherapy, the median time to next treatment was 22 months. To conclude, a late presentation and higher risk categories were common in our cohort of patients. Treatment outcome was comparable to those reported in western literature. RCD regimen was found to be a better treatment option in terms of overall survival.